Experimental evidence of a mixed breeding strategy and food-dependent maternal and larval traits in chub mackerel - Yoneda, Michio; Nakamura, Masahiro; Morioka, Taizo; Tsuzaki, Tatsuo; Togashi, Hiroyuki; Yukami, Ryuji (Frontiers in Marine Science, 2025)
Food availability plays a critical role in shaping reproductive success of small pelagic fishes, and in natural population, reduced prey access often arises under conditions of intra- and inter-specific density dependence. While energy allocation to egg production has often been viewed along a capital–income continuum, recent studies suggest that reproductive strategies may be more flexible or mixed than previously assumed. However, few studies have empirically examined how the timing and location of prey availability affect reproductive traits in the context of density-dependence. To address this gap, we conducted stable isotope tracer and controlled feeding experiments using chub mackerel (Scomber japonicus) to determine when and how feeding conditions influence reproductive output. A diet-switch experiment using carbon and nitrogen stable isotope ratios revealed much slower isotopic turnover in chub mackerel compared to income-breeding anchovy in similar experiments, suggesting that chub mackerel primarily rely on stored reserves (capital breeding), with limited reliance on dietary resources during spawning. Food restriction during the five months prior to spawning significantly reduced somatic condition and egg production in repeat spawners. Larvae from food-restricted females exhibited reduced growth and starvation tolerance compared to those from well-fed females. These findings demonstrate that maternal nutritional history has marked effects on both egg production and larval performance, highlighting the importance of considering energy allocation tactics when evaluating density-dependent reproduction. Our findings further provide a basis for discussing recent changes in the reproductive output of the Pacific stock of chub mackerel in the light of maternal nutritional history and its role in reproductive success.